2015
DOI: 10.3389/fpsyg.2015.01069
|View full text |Cite
|
Sign up to set email alerts
|

Emotional availability: theory, research, and intervention

Abstract: Attachment theory (Bowlby, 1969) and its limitations are first described. Next, emotional availability (EA; Biringen et al., 1998; Biringen, 2008) is introduced as an expansion upon the original conceptualization of the parent–child attachment relationship. As a construct and as a measure, EA considers the dyadic and emotional qualities of adult–child relationships. EA is predictive of a variety of child outcomes, such as attachment security, emotion regulation, and school readiness. Recently developed program… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
64
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 25 publications
(36 reference statements)
1
64
0
1
Order By: Relevance
“…Mothers with a higher educational level also were better in supporting and guiding child's learning by not only teaching and helping but also supporting independent learning, as described by Saunders et al. (), in children with OPD, mostly with regulatory problems or with those who were maltreated. Therefore, it seems that higher maternal education led to a more patient, supporting, and consistent mode of parenting.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Mothers with a higher educational level also were better in supporting and guiding child's learning by not only teaching and helping but also supporting independent learning, as described by Saunders et al. (), in children with OPD, mostly with regulatory problems or with those who were maltreated. Therefore, it seems that higher maternal education led to a more patient, supporting, and consistent mode of parenting.…”
Section: Discussionmentioning
confidence: 84%
“…Third, regression results indicated that higher maternal education was associated with higher sensitivity and less intrusiveness in the ASD and the DD groups, less hostility in the DD group, and more structuring in the OPD group. As defined by Saunders, Kraus, Barone, and Biringen (), sensitivity leads to creation and maintaining a positive, healthy connection with the child by the use of behaviors and emotions of an adult while nonintrusiveness refers to the ability of an adult to follow the child's lead during play and without interference. This suggests that mothers with higher education were better at creating a healthy connection without interference with infants who had significant social interaction problems and/or DD.…”
Section: Discussionmentioning
confidence: 99%
“…The caregiver's emotional availability is often used to assess the ability of the caregiver to help the infant self-regulate. Various treatment methods have been devised that teach the caregiver how to be sensitive and to identify infant needs and how to foster secure attachment, that is, provide a secure base from which the child can go off to explore (Saunders, Kraus, Barone, & Biringen, 2015;Welch & Ludwig, 2017b).…”
Section: Theories Underlying Current Carementioning
confidence: 99%
“…Recognition of both the importance of the dyad as the unit of analysis , and the need for relationship‐based assessments, has been evident in efforts to describe dyadic‐level constructs, such as synchrony, mutuality, emotional recognition and emotional availability . While each of the aforementioned dyadic‐level constructs is defined differently, the common thread that links these constructs is a similar, underlying pattern of connection between a caregiver and a child.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Saunders et al. described emotional availability as a shared dyadic emotional connection, encompassing proximity seeking and visual contact with a parent. While emotional availability is viewed as a dyadic‐level construct, investigators have questioned how the mutual component is addressed.…”
Section: Introductionmentioning
confidence: 99%